Electronic irradiation ageing in the vicinity of glass transition temperature for PEEK space applications - Rival, G.; Dantras, E.; Paulmier, T. (Polymer degradation and stability, 2020)
Satellites in space environment are subject to several environmental constraints. In the case of polymer materials, electronic irradiations can induce premature ageing which can lead to a shorter lifetime for the satellite. Moreover, synergistic effects between temperature and irradiation can occur and enhance this ageing. A previous study showed that PolyEtherEtherKetone (PEEK), a newly used polymer in space industry, presents great radiation tolerance properties. Nonetheless, it was necessary to investigate the influence of temperature factor on its ageing. This study focuses on the comparison of PEEK samples aged at two temperatures: room temperature and 165∘C. Irradiations have been performed under high-vacuum and with a mono-energetic electron beam. They led to doses representative of 15 years of exposure to geostationary electronic environment. The comparison between both types of samples showed that increase in irradiation temperature have a significant impact on ageing kinetics. In particular, analyses revealed a higher cross-linking density for 165∘C irradiated samples which has been associated with a higher recombination rate of radicals due to amorphous phase mobility increase above glass transition. •PolyEtherEtherKetone (PEEK) films were irradiated by electrons at two temperatures: room temperature and 165 °C.•Irradiated samples showed a higher cross-linking density associated with a higher recombination rate of radicals at 165 °C.•Competition between cross-linking and amorphisation has a significant impact on property evolutions.